Comparative Effectiveness of Multiple Psychological Interventions for Psychological Crisis in People Affected by Coronavirus Disease 2019: A Bayesian Network Meta-Analysis - Yang, Yang; Sun, Shaodan; Hu, Shaowen; Tang, Chunzhi; Zhang, Yimin; Lin, Haibo (Frontiers in Psychology, 2021)
Objective: The objective of our current research is to compare the different psychological interventions and distinguish the most effective way to treat psychological crisis according to different clinical manifestation in people affected by COVID-19. No previous systematic review has provided a comprehensive overview by performing a Bayesian network meta analysis of this current topic. Method: A systematic review and Bayesian network meta-analysis were conducted on randomized controlled trials, nonrandomized controlled trials, case-control studies, self controlled case series(SCCS), cohort studies and cross-sectional studies of all the available interventions for psychological crisis in people affected by COVID-19. We searched the electronic databases EMBASE, Pubmed, Web of Science, PsycINFO, Cochrane Library, as well as the Chinese databases such as Sinomed, Chinese Biomedicine Literature (CBM), Chinese Scientific Journal Database (VIP), WanFang Database and China National Knowledge Infrastructure (CNKI) from 2019 to April 30, 2020. The main outcomes were Self-Rating Anxiety Scale (SAS) , Self-Rating Anxiety Scale (SDS), patient health questionnaire (PHQ-9) and symptom check list (SCL-90). The study is registered with Inplasy, number 202050076. Result: 16 SCCS comprising 1147 participants compared 5 different psychological interventions with 4 different measurement scales were included in this study. For effectiveness, all the psychological therapies were significantly more effective than before intervention. Our results showed that supportive therapy(ST) which is adjusted to the COVID-19-related mental crisis is the best treatment compared with behaviour therapy(BT), nursing-based pshchological therapy(NBPT), traditional Chinese medicine therapy(TCMT), and COVID-19-related standard training (CRST) at reducing the anxiety-related symptoms assessed by SAS. When measured by SDS, BT was better than ST and NBPT treatment for reducing the depression symptoms. And ST was better than BT and ST+BT assessed by PHQ-9. In the end, the last network meta-analysis indicated that NBPT was more effective than ST by the measurement of SCL-90. Conclusion: Our research suggested the potential effectiveness of psychological interventions for decreasing psychological crisis in people affected by COVID-19 and try to introduce the best effective treatment options for clinical practice according to the clinical manifestations of psychological problems, but further confirmation from high quality RCTs are needed.